RANCANG BANGUN SISTEM PEMANTAUAN DAN PENGENDALIAN CAIRAN INFUS MELALUI DISPLAY KONTROL DAN APLIKASI MOBILE DI MASA PANDEMIC COVID-19 - RAJES KHANA; MUHAMMAD RIJALI (Universitas 17 Agustus 1945 Jakarta, 2020)
During the COVID-19 pandemic, nurses were overwhelmed to deal with sick patients and patients who were positively affected by the COVID-19 virus. Especially in sick patients with infusion needs in COVID-19 positive patients, which is not controlled due to the large number of patients. Along with that, the need for technology is needed in the medical world. With extensive hospital conditions, large patient numbers and limited medical personnel and the demands of good patient care are always a problem in every hospital. To solve the problem can be solved by creating a system of control and monitoring in real time by nurses without having to do a check manually. The system uses Arduino Uno microcontroller and Node MCU ESP 8266 with photodiode and photogate sensor, 2.4